Dietary Supplementation of Zinc to Improve Pacific White Shrimp (Litopenaeus vannamei) Immune System - Adni Oktaviana (Airlangga University, 2018)
This study aimed to determine the effect of zinc supplementation to improves immune responses on the pacific white shrimp (L. vannamei).This study consist of two treatments with four replicates. Dietary zinc supplementation 45 mg/kg of feed (P) anda without dietary zinc supplementation (C). This study was conducted for five weeks. The result showed significantly different on growth performance and haemocytes total. However, its has no significantly different on survival rate of the shrimp. Keywords: Pacific White Shrimp, Total Haemocyte Count, Zinc